Coping with Institutional and Financial Crises in the Sixteenth and Seventeenth Centuries: Ensuring the Survival of Ottoman Royal Waqfs. (November 2019) - Orbay, Kayhan
The Ottoman Empire had inherited the waqf (charitable foundation) as an institutionalized form of charity from the Near Eastern Islamic states, which had preceded it. Over time, new forms of charitable foundations emerged, while with the expansion of the Empire, waqfs grew in number and spread geographically. Donors created over fifty thousand charitable foundations, making them into the most widespread institution in Ottoman history. Some waqfs, the largest ones in particular, survived for many centuries. However, sometimes continued functioning was under severe threat, due to wars, epidemics, natural disasters, and rebellions. To overcome financial straits, the waqfs resorted to a variety of measures. Occasionally, a royal waqf in difficulty received assistance from other foundations established by sultans and/or their relatives. Administrators reduced current expenditures, sometimes even suspending salaries and charitable services. Moreover, through long-term lease contracts involving substantial down payments by the lessees, waqf administrators often raised the money needed to restore damaged properties. In the present paper, we study Ottoman royal waqfs when exposed to adversities and financial hardships. As administrators reacted with considerable flexibility, the claim that the waqfs were rigid institutions is in obvious need of revision.